Sc/C codoping effect on the electronic and optical properties of the TiO2 (101) surface: a first-principles study. Issue 50 (24th September 2021) - Li, Dongxiang; Li, Ruiqin; Zeng, Fanjin; Wang, Shuyi; Yan, Wanjun; Deng, Mingsen; Cai, Shaohong
Abstract : The Sc/C-codoped TiO2 (101) surface with 5.56% impurity concentration exhibited optimal photocatalytic performance in the visible region, which may be helpful for designing the high-performance of photocatalysts by doping. Abstract : Extension of the light absorption range and a reduction of the possibility of the photo-generated electron–hole pair recombination are the main tasks to break the bottleneck of the photocatalytic application of TiO2 . In this paper, we systematically investigate the electronic and optical properties of Sc-doped, C-doped, and Sc/C-codoped TiO2 (101) surfaces using spin-polarized DFT+U calculations. The absorption coefficient of the Sc/C-codoped TiO2 (101) surfaces were enhanced the most compared with the other two doped systems in the high energy region of visible light, which can be attributed to the shallow impurity states. Furthermore, we studied the optical absorption properties with the change of the impurity concentration. The Sc/C-codoped TiO2 (101) surface with 5.56% impurity concentration exhibited optimal photocatalytic performance in the visible region. These results may be helpful for designing the high-performance of the photocatalysts by doping.